2018
DOI: 10.5858/arpa.2018-0147-oa
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence–Based Breast Cancer Nodal Metastasis Detection: Insights Into the Black Box for Pathologists

Abstract: Context.-Nodal metastasis of a primary tumor influences therapy decisions for a variety of cancers. Histologic identification of tumor cells in lymph nodes can be laborious and error-prone, especially for small tumor foci.Objective.-To evaluate the application and clinical implementation of a state-of-the-art deep learning-based artificial intelligence algorithm (LYmph Node Assistant or LYNA) for detection of metastatic breast cancer in sentinel lymph node biopsies.Design.-Whole slide images were obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
245
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 317 publications
(253 citation statements)
references
References 24 publications
2
245
0
6
Order By: Relevance
“…1 For example, ML algorithms have been applied to great success in GWAS, and have proven effective at detecting patterns of epistasis within the human genome. 2 Recently, deep learning algorithms were used to detect cancer metastases on high-resolution pathology images 3 at levels comparable to human pathologists. These results, among others, indicate heavy interest in ML development and analysis for bioinformatics applications.…”
Section: Introductionmentioning
confidence: 99%
“…1 For example, ML algorithms have been applied to great success in GWAS, and have proven effective at detecting patterns of epistasis within the human genome. 2 Recently, deep learning algorithms were used to detect cancer metastases on high-resolution pathology images 3 at levels comparable to human pathologists. These results, among others, indicate heavy interest in ML development and analysis for bioinformatics applications.…”
Section: Introductionmentioning
confidence: 99%
“…OOF image artifacts can have even more severe consequences in automated image analysis by directly impacting detection and classification. Some studies found that systematic errors can be attributed to suboptimal focus quality, such as OOF germinal centers being mistaken for tumor metastases by an algorithm [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that it is beneficial to have more negative samples than positive samples in a training dataset for image classification in digital pathology 29,[46][47][48] . A good ratio of negative to positive samples (i.e., patches in our case) will increase the generalization of a CNN model and decrease false positive rate.…”
Section: Patch Extraction For the Breast Cancer Datasetmentioning
confidence: 99%